2006
DOI: 10.1103/physrevd.73.126011
|View full text |Cite
|
Sign up to set email alerts
|

NewG2holonomy metrics, D6 branes with inherentU(1)×U(1)isometry,

Abstract: It is found the most general local form of the 11-dimensional supergravity backgrounds which, by reduction along one isometry, gives rise to IIA supergravity solutions with a RR field and a nontrivial dilaton, and for which the condition F 1;1 0 holds.This condition is stronger than the usual condition F ab J ab 0, required by supersymmetry. It is shown that these D6 wrapped backgrounds arise from the direct sum of the flat Minkowski metric with certain G 2 holonomy metrics admitting an U1 action, with a local… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Contracting (3.25) with w and using that the metric g 8 is S 1 -invariant we obtain 27) which implies…”
Section: Jhep05(2015)085mentioning
confidence: 84%
See 1 more Smart Citation
“…Contracting (3.25) with w and using that the metric g 8 is S 1 -invariant we obtain 27) which implies…”
Section: Jhep05(2015)085mentioning
confidence: 84%
“…For instance, in reference [24] it was shown that a configuration of D6-branes wrapping a special Lagrangian cycle of a non-compact Calabi-Yau manifold such that the internal string frame metric is Kähler, is dual to a purely geometrical background in eleven dimensions with an internal metric of G 2 -holonomy. Other examples of torsion-free structures dual to configuration with fluxes, in other words, non-zero torsion, can be found in references [25][26][27][28], this time from six-dimensions to a G 2 -holonomy. For further examples and results in the Spin(7) and G 2 cases see reference [29,30].…”
Section: Jhep05(2015)085mentioning
confidence: 99%
“…One is that κ = α, in which case the solution is completely determined by one basic equation for G, given by (36). The other is that κ = 0, in which case the solution is completely determined by the basic equation (46).…”
Section: Case Ii: κ 1 =mentioning
confidence: 99%
“…Examples of complete metrics on non-compact manifolds in higher dimensions with G 2 and spin (7) holonomy were constructed in the later 1980s [16][17][18][19]. Inspired by the AdS/CFT correspondence and applications in M-theory compactification, large classes of explicit metrics on G 2 and spin (7) holonomy spaces have been constructed and their applications in string and M-theory have been discussed [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%